Evektifitas Penyinaran Untuk Peningkatan Produksi Buah Naga: Lighting Effectiveness to Increase Dragon Fruits Production - Cindy Ineke Ferdianti; Sudarti (Agrifarm : Jurnal Ilmu Pertanian, 2021)
Dragon fruit has a fairly high economic value, but its productivity is still seasonal, so it can be harvested at the same time lowering prices. This study aims to test the effectiveness of lighting in increasing the productivity of dragon fruit. This research was conducted through a survey with respondent dragon fruit farmer who use lighting and not. The sample of this research is dragon fruit tree which consists of 50 trees that are illuminated and 50 trees that are not. As an indicator of dragon fruit productivity, dragon fruit and flowers were counted during the study. The research data were analyzed using T-Test analysis to produce dragon fruit tree productivity between the two sample groups. The results of `this study showed that the productivity of dragon fruit in the without lighting group produced an average of 4 fruits and in the lighting group produced an average of 8 fruits. Flower productivity in the without lighting group produced an average of 6 flowes and in the lighting group an average of 21 flowers. Giving light in dragon fruit farming is effective in increasing productivity. Keyword: Dragon fruit, lighting, productivity